POS Tagging and Lemmatization of Historical Varieties of Languages. The Challenge of Old Italian - Manuel Favaro; Marco Biffi; Simonetta Montemagni (IJCoL)
The paper discusses the challenges of POS tagging and lemmatization of historical varieties of Italian, and reports for both tasks the results of experiments carried out in a classical supervised domain adaptation scenario using the diachronic and typologically differentiated corpus built for the "Vocabolario Dinamico dell’Italiano Moderno" (VoDIM). For what concerns POS tagging, the effectiveness of retrained models is illustrated and substantiated with quantitative data, with a specific view to linguistic annotation results obtained with respect to specific language evolution stages, domains and textual genres. For lemmatization, different customized models have been developed, including lexicon-assisted ones and models retrained with historical annotated texts. In both cases, a detailed error analysis is provided.